2019
DOI: 10.1101/609438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging-related inflammation driven by cellular senescence enhances NAD consumption via activation of CD38+pro-inflammatory macrophages

Abstract: Decline in tissue NAD levels during aging is linked to aging and its associated diseases. However, the mechanism for aging-associated NAD decline remains unclear. Here we report that pro-inflammatory M1-like macrophages, but not naïve or M2 macrophages, accumulate in metabolic tissues including visceral white adipose tissue and the liver during aging. Remarkably, these M1-like macrophages highly express the NAD consuming enzyme CD38 and have enhanced CD38-dependent NADase activity. We also find that senescent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 89 publications
0
28
0
Order By: Relevance
“…Low levels of NAD + were also reported in several tissues (Massudi et al, 2012;Zhu et al, 2015), and supplementation of NAD + precursors increased life span in different species (Fang et al, 2016;Zhang et al, 2016). Interestingly, SCs were shown to induce the SASP-mediated expression of CD38 -an ectoenzyme with a high NADase activity -in non-senescent cells, such as endothelial cells and bone marrow-derived macrophages (Chini et al, 2019;Covarrubias et al, 2019). CD38 inhibitors rescued NAD + decline and ameliorated a number of age-related metabolic outcomes in mice (Tarrago et al, 2018).…”
Section: Me1mentioning
confidence: 94%
“…Low levels of NAD + were also reported in several tissues (Massudi et al, 2012;Zhu et al, 2015), and supplementation of NAD + precursors increased life span in different species (Fang et al, 2016;Zhang et al, 2016). Interestingly, SCs were shown to induce the SASP-mediated expression of CD38 -an ectoenzyme with a high NADase activity -in non-senescent cells, such as endothelial cells and bone marrow-derived macrophages (Chini et al, 2019;Covarrubias et al, 2019). CD38 inhibitors rescued NAD + decline and ameliorated a number of age-related metabolic outcomes in mice (Tarrago et al, 2018).…”
Section: Me1mentioning
confidence: 94%
“…However, the mortality rate for obese elderly adults with COVID-19 was approximately 14% [72]. In addition to obesity, Covarrubias and colleagues found that during aging senescent cells significantly accumulate in visceral white adipose tissue and inflammatory cytokines found in the supernatant from senescent cells, which are induced macrophages to proliferate and to express CD38, as a T cell activation marker [73]. Alicka and colleagues in 2020 found that adipose-derived stem cells from older groups exhibited increased gene expression of pro-inflammatory gene and miRNAs (such as IL-8, IL-1β, TNF-α, miR-203b-5p, and miR-16-5p), and apoptosis markers (such as p21, p53, caspase-3, caspase-9) [69].…”
Section: Aging and Senescent Adipocytesmentioning
confidence: 99%
“…Furthermore, eliminating this subset of so-called senescent-like or pseudo senescent macrophages with an M2 phenotype induces a striking resolution of inflammation [69]. Recent work also shows that the SASP can promote macrophage proliferation and increased expression of CD38, which enhances the consumption of NAD by macrophages and might explain the age-related decline in NAD levels [70].…”
Section: Interaction Of Senescent Cells With Macrophagesmentioning
confidence: 99%